Mytheme and Motif: Lévi-Strauss and Wagner - Leavitt, John (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2010)
Starting with Claude Lévi-Strauss’s evaluation of Richard Wagner as “the undeniable father of the structural analysis of myth,” this paper compares Lévi-Strauss’s myth analysis with Wagner’s myth construction, arguing that each illuminates, clarifies, and potentially enriches the other.